Differential associations of ferritin and 25‐hydroxyvitamin D with fasting glucose and diabetes risk in community dwelling older men. Issue 7 (10th June 2019) - Carrivick, Simon; Alfonso, Helman; Golledge, Jonathan; Clancy, Paula; Flicker, Leon; Gunton, Jenny E.; Hankey, Graeme J.; Almeida, Osvaldo P.; Norman, Paul E.; Yeap, Bu B.
Abstract: Aims: We examined associations of ferritin and 25‐hydroxyvitamin D with fasting glucose and prevalent diabetes in older men. Methods: Cross‐sectional analysis of 4153 community‐dwelling men aged 70 to 89 years in Western Australia. Plasma ferritin, 25‐hydroxyvitamin D, and glucose were assayed. Diabetes was ascertained from self‐report, medications, and fasting glucose. Results: There were 577 men with diabetes (13.9%). In the whole cohort, ferritin was associated with fasting glucose (0.051 mmol/L per 1 SD increase in ferritin, P  = .006) and 25‐hydroxyvitamin D was inversely associated (−0.085 mmol/L per 1 SD, P  < .001). Ferritin was not associated with prevalent diabetes (highest vs. lowest quartile; >225 vs <66 μg/L: adjusted odds ratio [OR] 0.97, 95% confidence interval [CI], 0.74‐1.27, P  = .83). Higher vitamin D was associated with decreased odds of prevalent diabetes (highest vs lowest quartile; >82 nmol/L vs <53 nmol/L: OR = 0.57, 95% CI = 0.43‐0.75, P  < .001). There was no interaction between ferritin and vitamin D on diabetes risk. Conclusions: In older men, ferritin is associated with fasting glucose but not prevalent diabetes. Higher 25‐hydroxyvitamin D concentrations are independently associated with lower fasting glucose and reduced risk of diabetes. Clinical trials are required to determine whether interventions, which raise vitamin D concentrations, would reduce incidence of diabetes in this expanding demographic group.